2019
DOI: 10.3390/genes10100778
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Markers for Pan-Cancer Prediction by Deep Learning

Abstract: For cancer diagnosis, many DNA methylation markers have been identified. However, few studies have tried to identify DNA methylation markers to diagnose diverse cancer types simultaneously, i.e., pan-cancers. In this study, we tried to identify DNA methylation markers to differentiate cancer samples from the respective normal samples in pan-cancers. We collected whole genome methylation data of 27 cancer types containing 10,140 cancer samples and 3386 normal samples, and divided all samples into five data sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 26 publications
0
57
0
Order By: Relevance
“…Prior works that have explored pan-cancer prediction in the deep learning space have limited their analyses to a small set of CpGs that do not capture a holistic understanding of interaction and regulation in the cancer context [44]. Our results demonstrate that models with a larger number of CpGs are needed to accurately capture differences in tissue/cancer subtypes.…”
Section: Discussionmentioning
confidence: 89%
“…Prior works that have explored pan-cancer prediction in the deep learning space have limited their analyses to a small set of CpGs that do not capture a holistic understanding of interaction and regulation in the cancer context [44]. Our results demonstrate that models with a larger number of CpGs are needed to accurately capture differences in tissue/cancer subtypes.…”
Section: Discussionmentioning
confidence: 89%
“…Aberrant DNA methylation modifications are frequently detected in various tumors, and the main mechanisms for DNA methylation-involved tumorigenesis are that methylation levels of the promoter region of anti-oncogene are elevated, which promotes the key anti-oncogene silencing and drives tumorigenesis. 12,[14][15][16] MBD2 has been reported in multiple human malignancies, including gastric cancer, 17 breast cancer, 18,19 colorectal cancer, 20 glioblastoma, 21,22 hilar cholangiocarcinoma, 23 hepatocellular carcinoma, 24,25 chronic myeloid leukemia 26 and prostate cancer. 27 Previous studies confirmed that MBD2 mediates the transcriptional repression of tumor suppressor genes, such as hTERT, 28 GSTP1, 29 BAI1, 21 p14 ARF /p16 INK4a,30 and 14-3-3sigma, 27 which supports the pivotal role of MBD2 in abnormal epigenetic regulation of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an accuracy of 0.961 is obtained by Tang et al, in multiclass classification of 14 tissue types [19]. Liu et al reaches a ROC AUC of 0.989 with multiclass classification of eight cancer types, where some samples are from TCGA [20]. These recent studies demonstrate that machine learning approaches can be used to classify cancer based on DNA methylation data, even when using a highly-filtered small probe list [21,20,19,18].…”
Section: Discussionmentioning
confidence: 94%
“…Liu et al reaches a ROC AUC of 0.989 with multiclass classification of eight cancer types, where some samples are from TCGA [20]. These recent studies demonstrate that machine learning approaches can be used to classify cancer based on DNA methylation data, even when using a highly-filtered small probe list [21,20,19,18]. Multiple probe selection statistical methods were commonly used, such as LASSO, the moderated t-statistic, Maximum-Relevance-Maximum-Distance, and PCA.…”
Section: Discussionmentioning
confidence: 99%